ERS International Congress 2021: highlights from the Respiratory Clinical Care and Physiology Assembly. Issue 2 (23rd May 2022) - Gille, Thomas; Sivapalan, Pradeesh; Kaltsakas, Georgios; Kolekar, Shailesh B.; Armstrong, Matthew; Tuffnell, Rachel; Evans, Rachael A.; Vagheggini, Guido; Degani-Costa, Luiza Helena; Vicente, Cláudia; Das, Nilakash; Poberezhets, Vitalii; et al.
It is a challenge to keep abreast of all the clinical and scientific advances in the field of respiratory medicine. This article contains an overview of laboratory-based science, randomised controlled trials and qualitative research that were presented during the 2021 European Respiratory Society International Congress within the sessions from the five groups of the Assembly 1 – Respiratory clinical care and physiology. Selected presentations are summarised from a wide range of topics: clinical problems, rehabilitation and chronic care, general practice and primary care, electronic/mobile health (e-health/m-health), clinical respiratory physiology, exercise and functional imaging. This article provides an overview of some of the highlights from @ERSAssembly1 presented during the #ERSCongress 2021 https://bit.ly/3KPWZOc